Negotiating Historical Agency in Indonesian Comics: A Multimodal Discourse Analysis of Herman Johannes in Komando Rajawali - Triyadi Guntur Wiratmo; Yasraf Amir Piliang; Agung Eko Budi Waspada; Seno Gumira Ajidarma (International Journal Labs, 2026)
Comics have increasingly been recognized as multimodal cultural texts that combine visual and verbal elements to construct narrative meaning and ideological perspectives. Within historical comics, character representation plays an important role in shaping how historical actors and events are interpreted by audiences. However, studies examining how visual and verbal elements jointly articulate ideological meanings through character representation remain relatively limited, particularly in the context of Indonesian historical comics. This study aims to examine how the character Herman Johannes is represented in the comic Komando Rajawali 05: The Final Battle and how this representation contributes to the reinterpretation of historical narratives about the Indonesian independence struggle. Using a qualitative approach based on Multimodal Critical Discourse Analysis (MCDA), the study analyzes selected comic panels that depict Herman Johannes through the interaction of dialogue, visual composition, symbolic objects, and character gestures. The analysis reveals that the character is constructed as a civilian scientist whose intellectual expertise function as an alternative form of strategic contribution within the struggle of independence narrative. Visual elements such as books, spatial positioning, and gesture symbolism work together with verbal dialogue to redefine knowledge as a form of power alongside military action. These findings highlight the role of comics as cultural media capable of negotiating dominant historical narratives and expanding the representation of historical agency beyond military-centered perspectives in Indonesian independence discourse.